Psychometrics properties of the Team Interaction Scale and influencing factors of team interaction of tertiary hospital physicians in China: a cross-sectional study. Issue 8 (14th August 2019) - Song, Wenwen; Li, Honghe; Ding, Ning; Zhao, Weiyue; Shi, Lin; Wen, Deliang
Abstract : Objectives: To administer a cross-cultural adaptation of the Team Interaction Scale (TIS), test its psychometric properties and investigate influencing factors of team interactions in a physician population in Chinese tertiary hospitals. Design: Cross-sectional survey. Settings: Two rounds of surveys, a pilot and a large sampling survey, were conducted in two and nine tertiary hospitals, respectively, in Liaoning Province, China. Participants: In the pilot survey, 363 of 390 physicians sampled were included in the analysis, resulting in an effective response rate of 93.08%. In the large sampling survey, the effective response rate was 89.10% (3653 of 4100 physicians). Outcome measures: The TIS and a short version of a burn-out scale were administrated to assess the physician's team interaction and burn-out. Psychometric properties of TIS were tested by confirmatory factor analysis (CFA), exploratory factor analysis (EFA) and internal consistency analysis. Gender, age, discipline, education level, professional title, hospital scale and burn-out were explored as influencing factors with independent sample t -tests, one-way analyses of variance and a correlation analysis. Results: Based on CFA, a 17-item modified scale was developed following the pilot survey. In the large sampling survey, EFA was conducted with half of the samples, producing six dimensions: 'Communication', 'Coordination', 'Mutual help', 'Team goals', 'Work norms' and 'Cohesion and conflict resolution'. Fit of the modified model was confirmed by CFA with the other half of the samples (root mean square error of approximation=0.067, Comparative Fit Index=0.98, Normed Fit Index=0.97, Goodness of Fit Index=0.94, Adjusted Goodness of Fit Index=0.92). A high Cronbach's α coefficient of 0.98 demonstrated reliability of the modified scale. The Team Interaction Score was significantly lower in younger physicians, in men, in paediatricians and in physicians from larger-scale tertiary hospitals. Team Interaction Scores were negatively associated with burn-out. Conclusions: The adapted TIS, containing 17 items and six dimensions, was reliable and valid for Chinese tertiary hospital physicians. To address physician burn-out, team interaction should be highlighted.